2021
DOI: 10.1186/s12891-021-04657-z
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Term outcomes following fresh-frozen humeral head osteochondral allograft reconstruction for reverse Hill Sachs lesion: a case series

Abstract: Background Locked posterior glenohumeral dislocations with a reverse Hill-Sachs impaction fracture involving less than 30% of the humeral head are most frequently treated with lesser tuberosity transfer into the defect, whereas those involving more than 50% undergo humeral head arthroplasty. Reconstruction of the defect with segmental femoral osteochondral allografts has been proposed to treat patients between these two ranges, but the medium−/long-term outcomes of this joint-preserving procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Patients with OCA for reverse Hill-Sachs lesions after acute locked posterior shoulder joint dislocation have significantly improved function, a low degree of osteoarthritis, and excellent clinical outcomes compared with preoperative results. 84,145 Riff et al 112 concluded that OCA was a feasible treatment option for humeral head osteochondral defects. Regarding OCA of the hip, Oladeji et al 100 (n = 10), Khanna et al 72 (n = 17), and Kosashvili et al 73 (n = 8) analyzed the clinical and radiological results of OCA in patients with sizable femoral head osteochondral defects and considered fresh OCA (OCA using a freshly preserved graft) a reasonable choice for young patients with hip cartilage defects.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with OCA for reverse Hill-Sachs lesions after acute locked posterior shoulder joint dislocation have significantly improved function, a low degree of osteoarthritis, and excellent clinical outcomes compared with preoperative results. 84,145 Riff et al 112 concluded that OCA was a feasible treatment option for humeral head osteochondral defects. Regarding OCA of the hip, Oladeji et al 100 (n = 10), Khanna et al 72 (n = 17), and Kosashvili et al 73 (n = 8) analyzed the clinical and radiological results of OCA in patients with sizable femoral head osteochondral defects and considered fresh OCA (OCA using a freshly preserved graft) a reasonable choice for young patients with hip cartilage defects.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to harvest a larger, single graft is also beneficial because of the paucity of surface area available to harvest multiple grafts. Other techniques to address large humeral head defects have been described, 3 , 4 , 7 , 10 , 13 , 20 , 21 , 23 but the “free-hand” nature of these techniques can be difficult to replicate, and it is challenging to adequately restore the chondral surface and subchondral bone of the humeral head. The “Elliptical BioHumi” technique for OAT of the humeral head simplifies a technically demanding procedure with a reproducible method for addressing large, oblong osteochondral defects and potentially offers improved patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Treatment options are often based on the size of the reverse Hill-Sachs lesion, and many authors have recommended shoulder arthroplasty for impaction fractures that involve more than 50% of the humeral head. 3 , 4 The management of a reverse Hill-Sachs lesion involving less than 50% of the humeral head in younger patients is more controversial, and joint preservation techniques are favored over arthroplasty ( Fig 1 ). Multiple surgical procedures have been described, ranging from transposition of the subscapularis tendon with or without the lesser tuberosity into the defect, disimpaction and bone grafting, rotational osteotomy of the proximal humerus, and reconstruction with an osteochondral allograft.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martinez reported outcomes in 6 patients, with satisfactory outcomes in only 3 patients and advanced osteoarthritis or allograft collapse in the others 64 . In contrast, Marcheggiani Muccioli et al reported a low graft resorption rate with excellent patient-reported and clinical outcome measures in 12 of 12 patients at mean 5.5-year follow-up 65 .…”
Section: Rhsls and Bipolar Bone Lossmentioning
confidence: 91%